2017
DOI: 10.1007/s00246-017-1573-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased Atrial β-Adrenergic Receptors and GRK-2 Gene Expression Can Play a Fundamental Role in Heart Failure After Repair of Congenital Heart Disease with Cardiopulmonary Bypass

Abstract: Surgeries to correct congenital heart diseases are increasing in Brazil and worldwide. However, even with the advances in surgical techniques and perfusion, some cases, especially the more complex ones, can develop heart failure and death. A retrospective study of patients who underwent surgery for correction of congenital heart diseases with cardiopulmonary bypass (CPB) in a university tertiary-care hospital that died, showed infarction in different stages of evolution and scattered microcalcifications in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…As a matter of fact, the number of beta adrenoreceptors present at atrial level is the same as at ventricles. 21,22 In the present study, we found an impairment of RA conduit phase (RA e e ) in TS patients in comparison with control groups. RA e e represents passive filling of blood from systemic veins during ventricular diastole.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…As a matter of fact, the number of beta adrenoreceptors present at atrial level is the same as at ventricles. 21,22 In the present study, we found an impairment of RA conduit phase (RA e e ) in TS patients in comparison with control groups. RA e e represents passive filling of blood from systemic veins during ventricular diastole.…”
Section: Discussionsupporting
confidence: 52%
“…As a matter of fact, the number of beta adrenoreceptors present at atrial level is the same as at ventricles. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, our study is the first to analyze the behavior of β-ARs and GRKs in patients with congenital heart disease or with right ventricle disease in a stable situation. Only, one paper has been published analyzing alterations in the expression of GRK2 and ARs in atrial myocytes of patients with congenital heart disease operated on with cardiopulmonary bypass (Oliveira et al, 2017) but, in this case, the alterations were related to the vulnerability of the myocardium to catecholamine levels in an acute surgical context. These findings, although interesting, are not comparable to the situation of our patients, since post-RVP extraction has been performed in a stable situation, at least one year after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Once restored at room temperature, the sections were blocked with BSA and incubated with primary antibody overnight at 4 °C. The next day, the sections were incubated with secondary antibody at 37 °C in the dark for 1 h, and nuclei were stained with DAPI [20] , [21] . The fluorescent images were acquired by Tissue Gnostics AX10 analysis system (Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%